Symbolic violence against women: From domestic space to university: from home to university - Godinho, Maria Inês Almeida (Faculdade de Filosofia e Ciências, 2020)
In this text the objective is to analyze how the symbolic violence exerted against women in the family space extends to the Brazilian university academic. The hypothesis is that in this process the structures of male symbolic domination designed by the Brazilian patriarchal family over generations are reproduced, which makes this type of violence more subtle compared to physical violence, but no less devastating. Brazilian university students are constantly subjected to verbal abuse, humiliation, moral and psychological abuse by teachers, colleagues and staff who share the academic space with them, but such acts are recurrently naturalized by the perpetrators, and often by the victims themselves. for being impregnated in Brazilian society. The analysis relies mainly on Bourdieu's studies of male domination and symbolic power and violence. Submission: 2019-08-19